Fasting serum CGRP levels are related to calcium concentrations, but cannot be elevated by short-term calcium/vitamin D supplementation. (February 2015) - Hu, Fudong; Chen, Lianglong; Che, Hailan; Fang, Jun; Lv, Fenghua; Li, Hongjun; Zhang, Surong; Guo, Changlei; Yin, Honglei; Zhang, Shaoli; Zuo, Yulan
Highlights: First demonstration of the correlation between calcium and CGRP in heart disease. Inconsistent correlations between calcium and CGRP in diverse coronary diseases. Negative correlation may be associated with elevated natriuretic peptides. Fasting CGRP cannot be increased by short-term calcium supplementation. Abstract: Calcitonin gene-related peptide (CGRP) is an important cardioprotective neuropeptide. Few studies have shown that calcium supplementation may increase CGRP levels transiently. However, the relationship between CGRP and calcium is poorly known. This study was to explore the correlation between serum calcium and CGRP in coronary artery disease (CAD), and observe whether short-term calcium/vitamin D supplementation would increase fasting serum CGRP. A randomized, placebo-controlled and double-blind clinical trial, and a supplementary study for further analysis of the correlations were conducted. The results showed that the correlation between serum calcium and CGRP was positive in CAD without myocardial infarction (MI) ( r = 0.487, P = 0.029), but negative in acute and healing MI ( r = −0.382, P = 0.003). Moreover, we found a positive correlation between lg (amino-terminal pro-B-type natriuretic peptide, NT-proBNP) and CGRP ( r = 0.312, P = 0.027), but a negative correlation between lg (NT-proBNP) and serum calcium ( r = −0.316, P = 0.025) in acute and healing MI. As to the clinical trial, participants subjected to CAD but without evolving or acute MI, together with blood calcium ≤2.4 mmol/L, were randomized into three groups. Among the groups of placebo, caltrate (600 mg elemental calcium; 125 IU vitamin D3, per tablet) 1 tablet/d and caltrate 2 tablets/d, there were no significant differences in baseline characteristics. After short-term (5 days) treatments, the results indicated that the effect of grouping was not statistically significant ( P = 0.915). In conclusion, the correlations between serum calcium and CGRP in different types of CAD are inconsistent, and the main reason may be associated with elevated natriuretic peptides after acute MI. Further, our study shows that short-term calcium/vitamin D supplementation cannot significantly increase fasting serum CGRP levels.